Menopausal women requesting egg/embryo donation: examining health screening guidelines for assisted reproductive technology. Issue 7 (July 2016) - MacArthur, Taleen; Bachmann, Gloria; Ayers, Charletta
Abstract: Objective: As more postreproductive women opt to pursue pregnancy with advanced assisted reproductive technologies (ART), the menopausal practitioner will become more involved in counseling, screening, and referral of premenopausal, perimenopausal, and postmenopausal women for these services. This review was conducted with the aim of (1) evaluating ART screening practices as they pertain to postreproductive women, and (2) reviewing the outcomes of ART using oocyte donation in postreproductive women. Methods: A total of 950 unique records were found on PubMed, Clinical Key, and Google Scholar. Of these, 252 records were screened for relevance based on their titles and abstracts. With further review of these 252 records, 93 full-text articles were assessed for eligibility, and 63 were excluded based on relevance to our study. Finally, 30 studies were included in our qualitative synthesis. Results: Despite the increasing use of ART in postreproductive women, there are limited guidelines for determining candidacy with regard to maternal health, the most comprehensive of which are the guidelines from the American Society for Reproductive Medicine (ASRM). Although the American Society for Reproductive Medicine guidelines state that healthy women over 50 who are prepared for parenthood are candidates for ART through oocyte donation, they note that older women should be counseled as to the increased obstetric risk associated with advanced maternal age. With aging, particularly for those women who are menopausal and postmenopausal, the woman and her fetus, however, are at risk of increased morbidity and mortality as compared with younger, healthy pregnant women. Because national trends suggest that women are delaying childbearing, the cohort of postreproductive women looking toward ART using donor oocytes as a fertility option will expand and menopausal practitioners will often participate in the ART counseling of these women. Conclusions: Because maternal and fetal morbidity and mortality increase in postmenopausal women who become pregnant through ART, practitioners caring for this cohort should provide input into developing standardized, comprehensive guidelines for this population so that screening is consistent for all older women seeking this intervention and risks are objectively outlined and considered.